Dynamics of Innovation in the Context of Education and Local Economy: a Study on Creative Learning and Empowerment of Small Businesses in Pasir Jambu Sukaraja Bogor Village - Magdalena, Maria; Harini, Sri; Asmin, Erny Amriani; Pratama, Chandra Putra; Muhamad Risqi Pajar Pratama; Hadawiah, Nisa Siti Al; Andiza, Zhahra Yasmin Latiefa; Fauziah, Siti Rosmalia; Farhani, Aulia Nurul; Agustian, Muhammad Rianto; Ramadhani, Agung Putra (Asian Journal of Community Services, 2024)
This research delves into the study of innovation dynamics in the context of education and the local economy in Pasir Jambu Village, Sukaraja, Bogor. The study focuses on two main aspects: creative learning and the empowerment of small businesses in the rural community. Through a careful qualitative approach, we explore the role of innovation in stimulating local economic growth and improving the quality of education. The research findings indicate that creative learning in the schools of Pasir Jambu Village has had a positive impact on students' critical and creative thinking abilities. Teachers implementing innovative teaching methods have helped unleash students' potential in various academic and non-academic aspects. On the other hand, the empowerment of small businesses through various innovative initiatives has enhanced the productivity and competitiveness of small business owners in this village.